The Tianlai dish array low-z surveys forecasts. Issue 3 (8th October 2022) - Perdereau, Olivier; Ansari, Réza; Stebbins, Albert; Timbie, Peter T; Chen, Xuelei; Wu, Fengquan; Li, Jixia; Marriner, John P; Tucker, Gregory S; Cong, Yanping; Das, Santanu; Li, Yichao; et al.
ABSTRACT: We present the science case for surveys with the Tianlai dish array interferometer tuned to the [1300, 1400] MHz frequency range. Starting from a realistic generation of mock visibility data according to the survey strategy, we reconstruct maps of the sky and perform foreground subtraction. We estimate the level of residuals from imperfect subtraction, mostly due to mode mixing, i.e. distortions in the reconstructed 3D maps due to frequency-dependent instrument response. We show that a survey of the North Celestial Polar cap during a year of observations, covering an area of $150 \, deg^2$, would reach a sensitivity of $1.5-2 \, mK$ per $1 \, MHz × 0.25^2 \, deg^2 $ voxel and be marginally impacted by mode mixing. Tianlai would be able to detect ∼10 nearby massive H i clumps as well as a very strong cross-correlation signal of 21 cm intensity maps with the North Celestial Cap Survey optical galaxies. We also studied the performance of a mid-latitude survey, covering $\sim 1500 \, deg^2$ overlapping the SDSS footprint. Despite a higher noise level for the mid-latitude survey, as well as significant distortions due to mode mixing, Tianlai would be able to detect a highly significant cross-correlation between the 21 cm signal and the Sloan spectroscopic galaxy sample. Using the extragalactic signals measured from either or both of these surveys, and comparing them with simulations such as those presented here will make it possible to assess the impact of various instrumental imperfections on the Tianlai dish array performance. This would pave the way for future intensity mapping surveys with higher sensitivity.